The constant term in a complete square is the square of half the x coefficient.

X^2 + 3x - 5 = 0

x^2 + 3x = 5 (add 5 to both sides)

x^2 + 3x + (3/2)^2 = 5 + (3/2)^2 (complete the square on the left, add the same amount on the right so the equal sign is still true)

(x + 1.5)^2 = 5 + 2.25 (show the square, change to decimal for clarity)

x + 1.5 = ±√7.25 (square root both sides. Note we need ± .)

X^2 + 3x - 5 = 0

x^2 + 3x = 5 (add 5 to both sides)

x^2 + 3x + (3/2)^2 = 5 + (3/2)^2 (complete the square on the left, add the same amount on the right so the equal sign is still true)

(x + 1.5)^2 = 5 + 2.25 (show the square, change to decimal for clarity)

x + 1.5 = ±√7.25 (square root both sides. Note we need ± .)

**x = -1.5 ± √7.25**(subtract 1.5 from both sides)